Multiplication tips - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Rapid multiplication of Cassava. A color pocketbook. 1998. 61 pp. ISBN 978 131 133 9 Training Program IITA PMB 5320, Ibadan Nigeria.